Accelerated methane storage in clathrate hydrates using mesoporous (Organo-) silica materials - Nithin B. Kummamuru; Geert Watson; Radu-George Ciocarlan; Sammy W. Verbruggen; Pegie Cool; Pascal Van Der Voort; Patrice Perreault (Fuel, 2023)

Evolving Perspectives of Stewardship in the Seafood Industry - Robert Blasiak; Alice Dauriach; Jean-Baptiste Jouffray; Carl Folke; Henrik Österblom; Jan Bebbington; Frida Bengtsson; Amar Causevic; Bas Geerts; Wenche Grønbrekk; Patrik J. G. Henriksson; Sofia Käll; et al. (Frontiers in Marine Science, 2021)
Humanity has never benefited more from the ocean as a source of food, livelihoods, and well-being, yet on a global scale this has been accompanied by trajectories of degradation and persistent inequity. Awareness of this has spurred policymakers to develop an expanding network of ocean governance instruments, catalyzed civil society pressure on the public and private sector, and motivated engagement by the general public as consumers and constituents. Among local communities, diverse examples of stewardship have rested on the foundation of care, knowledge and agency. But does an analog for stewardship exist in the context of globally active multinational corporations? Here, we consider the seafood industry and its efforts to navigate this new reality through private governance. We examine paradigmatic events in the history of the sustainable seafood movement, from seafood boycotts in the 1970s through to the emergence of certification measures, benchmarks, and diverse voluntary environmental programs. We note four dimensions of stewardship in which efforts by actors within the seafood industry have aligned with theoretical concepts of stewardship, which we describe as (1) moving beyond compliance, (2) taking a systems perspective, (3) living with uncertainty, and (4) understanding humans as embedded elements of the biosphere. In conclusion, we identify emerging stewardship challenges for the seafood industry and suggest the urgent need to embrace a broader notion of ocean stewardship that extends beyond seafood.